Small-strain stiffness and damping of Lanzhou loess. Issue 95 (April 2017) - Song, Binghui; Tsinaris, Angelos; Anastasiadis, Anastasios; Pitilakis, Kyriazis; Chen, Wenwu
Abstract: This study examines the small-strain stress-strain properties during cyclic loading of Lanzhou loess deposits, characterized by a very high void ratio (>0.9). Torsional resonant column (RC) tests are performed in order to investigate the effect of water content, confining pressure, consolidation time and soil structure strength on the small-strain stiffness ( G 0 ) and damping (Dmin ) of loess. It is proved that shear modulus G 0 at low strain levels is very sensitive to water content while the effect of water content on small-strain damping Dmin is relatively small. As water content W approaches the plastic limit PL, there is a dramatic decrease of G 0 compared to drier loess specimen; G 0 has the tendency to reach a stable or constant value with further increase of water content which is more than the PL of loess. The small strain damping Dmin decreases continuously with water content for unsaturated loess and then tends to increase slightly for almost fully saturated loess. A linear relationship between G 0 and confining pressure σ′m in log-log coordinates for different water contents is observed for Lanzhou loess. Similarly, Dmin decreases linearly with σ′m . A power function is proposed to describe the relationship between G 0 and confining pressure σ′m where the exponent m varies with the water content of loess. G 0 is also affected by the consolidation duration and a power function is proposed between normalized G 0 and normalized consolidation time. G 0 is finally strongly affected by the structure of loess and the type of specimen. For undisturbed loess samples, G 0 is always higher than reconstituted ones and the difference decreases with the degree of saturation; for fully saturated samples the influence of the structure strength between undisturbed and reconstituted samples becomes insignificant. Likewise, Dmin of undisturbed loess is higher than that for remolded loess under the same confining pressure and the difference between them reduces with the degree of saturation as well. Highlights: We examined the small-strain dynamic properties of Lanzhou loess with metastable structure and high void ratio (>0.9). We found shear modulus G 0 of Lanzhou loess is more sensitive to water content than damping Dmin . A power function is proposed to describe the relationship between G 0 and confining pressure σ′m . The power equation proposed by Shibuya et al.[44] is suited to estimate the time-dependent increase of G 0 for loess. The small-strain dynamic properties ( G 0 and Dmin ) of undisturbed loess are higher than for remolded loess.